Geology, Mantle Tomography, and Inclination Corrected Paleogeographic Trajectories Support Westward Subduction During Cretaceous Orogenesis in the North American Cordillera - Hildebrand, Robert (Geoscience Canada, 2014)
Geological evidence, including the presence of two passive margin platforms, juxtaposed and mismatched deformation between North America and more outboard terranes, as well as the lack of rift deposits, suggest that North America was the lower plate during both the Sevier and Laramide events and that subduction dipped westward beneath the Cordilleran Ribbon Continent (Rubia). Terranes within the composite ribbon continent, now present in the Canadian Cordillera, collided with western North America during the 125–105 Ma Sevier event and were transported northward during the ~80–58 Ma Laramide event, which affected the Cordillera from South America to Alaska. New high-resolution mantle tomography beneath North America reveals a huge slab wall that extends vertically for over 1000 km, marks the site of long-lived subduction, and provides independent verification of the westward-dipping subduction model. Other workers analyzed paleogeographic trajectories and concluded that the initial collision took place in Canada at about 160 Ma – a time and place for which there is no deformational thickening on the North American platform – and later farther west where subduction was not likely westward, but eastward. However, by utilizing a meridionally corrected North American paleogeographic trajectory, coupled with the geologically most reasonable location for the initial deformation, the position of western North America with respect to the relict superslab parsimoniously accounts for the timing and extents of both the Sevier and Laramide events.